Charly [videorecording (DVD)] - Nelson, Ralph, 1916-1987; Bloom, Claire, 1931-; Robertson, Cliff, 1923-2011; Keyes, Daniel (MGM DVD., 2004)
A mentally challenged man becomes a genius after experimental brain surgery, developing a romance with his former special-education teacher before lapsing back into retardation.